2013
DOI: 10.3892/ijmm.2013.1577
|View full text |Cite
|
Sign up to set email alerts
|

Mammalian diaphanous-related formin 1 is required for motility and invadopodia formation in human U87 glioblastoma cells

Abstract: Abstract. Characterized by invasive growth and infiltrative dissemination, glioma is poorly diagnosed and prognosed at present. The mammalian diaphanous-related formin 1 (mDRF1), which is involved in a number of actin-related biological processes, has been found to participate in the process of invasion and metastasis in human breast cancer cells and to show abnormal expression under pathological conditions. However, the role of mDRF1 in glioma is not clear. In this study, we carried out a comprehensive analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 25 publications
2
12
0
Order By: Relevance
“…We also found that two additional MMPs expressed in the AC, zmp-3 and zmp-6 , were dependent on nhr-67 (Figure 4A and 4B). Finally, we examined the expression of actin regulators that promote invasive cellular behavior (Li et al, 2014; Wang et al, 2014). We found that AC expression of the actin regulators exc-6 (formin) and unc-34 (Ena/VASP) was dependent on NHR-67 activity, as RNAi depletion of nhr-67 resulted in reduced expression of exc-6 and unc-34 GFP transcriptional reporters (Figure 4A and 4B).…”
Section: Resultsmentioning
confidence: 99%
“…We also found that two additional MMPs expressed in the AC, zmp-3 and zmp-6 , were dependent on nhr-67 (Figure 4A and 4B). Finally, we examined the expression of actin regulators that promote invasive cellular behavior (Li et al, 2014; Wang et al, 2014). We found that AC expression of the actin regulators exc-6 (formin) and unc-34 (Ena/VASP) was dependent on NHR-67 activity, as RNAi depletion of nhr-67 resulted in reduced expression of exc-6 and unc-34 GFP transcriptional reporters (Figure 4A and 4B).…”
Section: Resultsmentioning
confidence: 99%
“…In parallel to the induction of cell invasion and ECM degradation by RTVP-1 we also found that RTVP-1 induced the formation of podosomes and invadopodia in glioma cells. In recent years it has become clear that invadopodia have an important role in the invasion of glioma [ 30 ], and several proteins which are involved in the formation of invadopodia in glioma cells have been further explored as potential therapeutic targets such as synaptojanin [ 42 ], diaphanous-related formin 1 [ 43 ], the small GTPase RhoG [ 44 ] and CRN2 [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that an actin-binding protein, cortactin, modulates the secretion and membrane expression of invadopodium-associated MMPs, including MMP-2 and MMP-9 in various cell types, such as vascular smooth muscle cells, head and neck squamous cell carcinomas, and breast cancer cells (22). As knockdown of mDia1 expression also reduces cortactin expression in malignant glioma cells (23), it is possible that mDia1 modulates MMP-2 and MMP-9 secretion via regulation of cortactin expression. In addition, results from the present study demonstrate that expression of MMP-2 is associated with breast cancer cell invasion induced by mDia1-CA (Fig.…”
Section: Mmp-2 Is Involved In Mda-mb-231 Cell Invasion Via Mdia1mentioning
confidence: 99%